Wastewater treatment by conversion of nitrogen-containing pollution by immobilized microbiocenosis in a biodisk installation - Iurchenko, Valentyna; Tsytlishvili, Kateryna; Malovanyy, Myroslav (Ecological Questions, 2022)
Experimental works are devoted to research the efficiency of deamonization and de-nitrogenation of wastewater during treatment in a biodisk installation. Working hypothesis - immobilization of the microbiocenosis can provide simultaneous deep treatment of wastewater from organic compounds and inorganic nitrogen-containing compounds. The purpose of this work is to assess the efficiency of purification of highly concentrated organic pollutants and mineralized wastewater from nitrogen compounds in a biodisk installation and to determine the main ecological-trophic groups of microorganisms included in the immobilized nitrogen-transforming microbiocenosis. Methods of research of immobilized microbiocenosis - microbiological. physiological, biochemical (inhibitory experiments), natural and model wastewater - hydrochemical. It has been established that in microbiocenosis immobilized on disks conditions that allow heterotrophic and autotrophic microorganisms to actively metabolize organic and inorganic compounds under aerobic and anoxidic conditions are created. The quantitative indicators of the influence on the kinetics of the processes of the concentration of organic substances in the treated wastewater have been determined. On the basis of microbiological, physiological and biochemical studies in the immobilized microbiocenosis, ammonium-acid bacteria (and, possibly, archaea) nitrite-acid and denitrifying bacteria were found, and in the absence of organic substances in the environment - anammox bacteria. Moreover, in the biofilm that was formed in the absence of organic substances in the environment, the activity of anammox bacteria in deamonization significantly exceeded the activity of ammonium oxidizing bacteria and archaea. The obtained results and quantitative requirements were used in the organization of real wastewater treatment in a biodisc plant in industrial conditions.